Lathyrism and the half-life of collagen - Taverne Aart A. R. (Sciendo, 1991)
Maturation of collagen in the periodontal ligament has often been designated as the cause of tooth eruption. The fact that collagen has a high turnover rate provided some sort of proof of this hypothesis. It is well known that lathyrogens decrease eruption rate. Experiments were performed, using Wistar rats, which looked into the relationship between collagen turnover and lathyrism. The collagen turnover was established in teeth not erupting after the administration of lathyrogens. These results were compared to those obtained after having stopped eruption by the placement of a goldcrown on the lower incisors. It was found that lathyrism, and therefore collagen maturation, did not influence turnover rate. Thus the supposition, that collagen is responsible for tooth eruption, becomes doubtful.